Participatory planning and the new ATER/ATES: An assessment of the challenges of implementation - Meyer, Leandro Frederico Ferraz; Pinto, Wilza da Silveira (Seven Editora, 2024)
The article submits our reflections on the challenges of participatory planning and collective management of ATER/ATES services in agrarian reform settlements. The Bloomington School's conceptual framework of institutional economics is employed to interpret these challenges as problems of polycentric governance and collective action for the provision of public goods and management of commonly-owned resources. The Habermasian critique of the limits of the conception of instrumental rationality is incorporated into the analysis to broaden the understanding of the different modes of engagement in the dialogical processes of participation. Based on an integrative scheme of the two approaches and results of previous research, the article concludes by stating the impossibility of replacing the internal willingness to cooperate with institutional engineering schemes and external incentives. DOI:https://doi.org/10.56238/sevened2024.018-004